2016
DOI: 10.1177/0731121416662028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Individual- and National-Level Factors on Attitudes toward Intimate Partner Violence

Abstract: The study evaluated if individual-and national-level factors influence intimate partner violence (IPV) attitudes. Using Demographic and Health Surveys' data, multilevel modeling was used to analyze 506,935 females nested in 41 nations. The results indicated that the respondents in nations with higher levels of gender inequality, measured by the Social Institutions and Gender Index, were more likely to agree a husband is justified to abuse his wife when she argues with him. National-level attitudes toward IPV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…Third, results suggested that countries with higher gender equality (i.e., equality between women and men in quality of knowledge, work, money, power, health, and time) were more likely to provide formal help, but no effects on informal and negative helping reactions to IPVAW were found. Substantial empirical data support the notion that IPVAW prevalence [ 3 , 13 , 39 ], as well as the justification of IPVAW [ 46 , 75 ], is significantly rooted in a gender inequality or larger power distance societies [ 34 ], however to our knowledge, we provide the first support linking gender-related macrosocial structural gender equality and the formal reaction to IPVAW within the European context. This result is particularly important because it reflects that living in a society that promotes and, indeed, consolidates gender equality by means of different domains (e.g., economy, political representation, and health status) models people’s helping attitudes and behaviors, specifically, those officially promoted by the government [ 76 ].…”
Section: Discussionmentioning
confidence: 52%
“…Third, results suggested that countries with higher gender equality (i.e., equality between women and men in quality of knowledge, work, money, power, health, and time) were more likely to provide formal help, but no effects on informal and negative helping reactions to IPVAW were found. Substantial empirical data support the notion that IPVAW prevalence [ 3 , 13 , 39 ], as well as the justification of IPVAW [ 46 , 75 ], is significantly rooted in a gender inequality or larger power distance societies [ 34 ], however to our knowledge, we provide the first support linking gender-related macrosocial structural gender equality and the formal reaction to IPVAW within the European context. This result is particularly important because it reflects that living in a society that promotes and, indeed, consolidates gender equality by means of different domains (e.g., economy, political representation, and health status) models people’s helping attitudes and behaviors, specifically, those officially promoted by the government [ 76 ].…”
Section: Discussionmentioning
confidence: 52%
“…There is a growing body of research, including some multi-country studies, on the structure of attitudes to DV at the individual or household level in low-and middle-income countries [ 2 – 12 , 18 21 ]. However, there is little cross-national country-level evidence [ 22 , 23 ] on how social, economic and political empowerment strategies, accepted as indicators of gender (in)equality influence the societal acceptability of DV. At the macro-level, Heise’s social ecological framework references gender norms including the acceptance of DV, systems that privilege men’s entitlement, rigid gender roles, masculinities linked to aggression and dominance, and honour as important drivers of violence against women [ 17 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of multicountry studies have focused on studying sociodemographic variables (eg, sex, age, marital status, residential area, education, number of children, working status, wealth status) at the individual and gender inequality at the country level. [16][17][18][19] Gender inequality, a set of structural features (eg, women and men's literacy, political power, health status, working status) which indicate gender power asymmetries in a country, have been linked to attitudes justifying IPVAW in different ways. Two studies showed that individuals in countries with higher levels of gender inequality were more likely to justify or accept IPVAW, 9 16 but others did not find such effect.…”
Section: Introductionmentioning
confidence: 99%